The Biology of the Red and Green Morphs of the Tobacco Aphid, Myzus Persicae Nicotianae (Blackman) on Flue-Cured Tobacco - Rhoda , Masukwedza; Upenyu , Mazarura; Peter , Chinwada; Susan, Dimbi (Asian Journal of Agriculture and Rural Development, 2013)
The tobacco aphid, Myzus persicae nicotianae is an economically important pest of tobacco. Damage is through direct injury by sucking sap of infested plants as well as reduction of the quality of the leaf by leaving honey-dew which encourages the subsequent growth of sooty-mould. In addition to this, aphids also transmit economically important virus diseases such as the bushy-top virus, the alfalfa mosaic virus and the potato virus-Y. Before 2002, the main colour form of the tobacco aphid in Zimbabwe was green. However, during the 2003/2004 tobacco season, concerns were raised where red forms of the tobacco aphid were observed to be more prevalent than the green form. During the 2004/2005 tobacco season, green forms of the tobacco aphid could only be found with difficulty. In intensive research spanning three years, the days to adulthood, days to 1st nymph, nymphs/day, longevity, fecundity and survival of the red morph were compared to that of the green aphid. Across all years, days to adulthood were the same for the two forms. The red morph produced more nymphs/day than the green morph. Longevity was similar but fecundity was 1½ to 2 times higher for the red morph than the green aphid. The red morph survived longer than the green aphid. These parameters combined to give the red morph of the tobacco aphid a greater reproductive potential and rate of population increase over the green morph thereby partly explaining the sudden increase in this pest in the recent past.